Impactos na percepção da cultura organizacional frente a mudança social em larga escala : adoção do teletrabalho na pandemia COVID-19 - Lima, Camila Raquel Lunardeli Fogaça (2022)
The Organizational Culture (OC) of a company is its identity and molds the behavior of its collaborators, and when well adjusted, it’s a fortress in its organizational strategy. Large-scale changes in society can impact OC, considering that it suffers from internal and external influences. One of the impacts of the COVID-19 pandemic was the adoption of telework due to social isolation. This measure made companies suddenly implement this work modality so that it was possible to get through this moment of sanitary crisis. When experiencing the benefits of telework, by both employee and employer, it’s perceived today that this work modality has become permanent. Considering these arguments, this research has the objective of analyzing the impact on OC's perception of collaborators facing this large-scale social change with employees currently using the telework modality. Based on Hofstede's OC concept, which defines the values of a company and its organizational practices as the manifestation of both.The Instrumento Brasileiro de Avaliação da Cultura Organizacional (IBACO) was used to collect colaborators data through an online survey research with 189 respondents. To investigate the hypothesis, using ANOVA tests, the differences between collaborators' OC perceptions were validated in different work modalities. It was also investigated if the collaborators that started working in the company before the pandemic, with presential contact with the OC, had different perceptions than colaborators hired during the pandemic. As a result, it was not proven a different perception of the OC between diffent work modalities, due to the quick company's response in adapting its OC to the new scenery. It was confirmed that time working in the company, that being, the professionals that ingressed before the pandemic, had a negative impact on the OC perception. The relation between OC variables was confirmed, identifying cooperative professionalism as the one with a higher degree of intermediation. It was concluded that OC adaptation is fundamental to mitigating the impacts that large-scale social changes can cause. When adopting telework it was important to make adjustments in the practices, considering that the relationship with the collaborator was changed due to the physical space modification caused by isolation.